Youth : volume two of the autobiographical trilogy - Tolstoy, Leo, graf, 1828-1910 (Open Road Integrated Media, 2017)
The third and final novel in Tolstoy's Autobiographical Trilogy, following Childhood and Boyhood. In Youth, Leo Tolstoy's protagonist-now a fervent sixteen-year-old-eagerly prepares to strike out on his own. And as he does so, he begins to savor life in all its glory, both grand and miniscule. From his interactions with friends, old and new, to his perceptions of the beauty of nature, the young man has an entirely new world to look forward to. But harsh lessons are waiting to teach him that far-flung expectations are rarely fulfilled to the dreamer's specifications, and that disappointment, anger, and grief are constant foes that must be contended with if one is to truly live. Youth concludes Tolstoy's semiautobiographical trilogy, originally planned as a four-part series of novels tentatively called the "Four Epochs of Growth." The completed works together form a remarkable expression of the great Russian novelist's early voice and vision, which would ultimately make him one of the most renowned and revered authors in literary history. This ebook has been professionally proofread to ensure accuracy and readability on all devices